2019
DOI: 10.24070/bjvp.1983-0246.v12i3p88-100
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antiparasitic action of essential oils of Lippia spp. in Koi Carp (Cyprinus carpio) fed supplemented diets

Abstract: This study evaluated the in vitro antiparasitic activity of the essential oils of Lippia alba, L. origanoides and L. sidoides against monogenean parasites of koi carp Cyprinus carpio and its zootechnical performance in net cages. The oils were obtained from the leaves by hydro distillation, and the chemical composition was evaluated via gas chromatography. In vitro assays were performed with each essential oil separately and combined in binary (1:1) and tertiary (1:1:1) mixtures with the Lippia species at 10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…[ 79 ]. Brasil, et al [ 9 ] researched anthelmintic effects of Lippia alba , Lippia origanoides , and Lippia sidoides EOs on Dactylogyrus minutus and Dactylogyrus extensus parasites; and they detected that when L. Origanoides and L. Sidoides EOs were applied as 100 mg/L for 5 min, they showed 100% efficacy ( Table 2 ).…”
Section: Essential Oils As Antiparasitic Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 79 ]. Brasil, et al [ 9 ] researched anthelmintic effects of Lippia alba , Lippia origanoides , and Lippia sidoides EOs on Dactylogyrus minutus and Dactylogyrus extensus parasites; and they detected that when L. Origanoides and L. Sidoides EOs were applied as 100 mg/L for 5 min, they showed 100% efficacy ( Table 2 ).…”
Section: Essential Oils As Antiparasitic Agentsmentioning
confidence: 99%
“…Due to the increase of consumer demand, aquaculture technique has been shifted from extensive to super-intensive; intensification of aquaculture needs a higher amount of artificial feed supply, water treatment and reuse, and high stocking density resulting in aquatic environmental degradation [ 4 , 5 , 6 ]. Mounting of stress and quality deterioration of living environment increases the activity and virulence of infectious and opportunistic microbial pathogens [ 7 ], decrease immunity and immune-related gene transcription of aquatic animals [ 8 ], and elevate uni and multicellular parasitic infestation [ 9 ]; finally, initiate infectious diseases outbreak along with the death of cultured species. Gonzales, et al [ 10 ] reported global aquaculture loss of 1.05 to 9.58 billion USD/year due to infectious diseases and parasitic attacks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Figure 1 shown the time for total immobilization of monogeneans in different concentrations of L. alba EO combined with silk fibroin. Lippia alba is an aromatic plant known for its EO, a compound with established antiparasitic activity against monogeneans of fish (Brasil et al, 2019;Soares et al, 2016). However, our previous study showed that in vitro exposure to 1280 and 2560 mg/L of L. alba EO dissolved in 70% ethyl alcohol caused 100% mortality of A. spathulatus, N. janauachensis and M.…”
Section: Ta B L Ementioning
confidence: 91%